Buenos Aires: An Art Metropolis in the Late Nineteenth Century - Baldasarre, Maria Isabel (2017)
This article focuses on the emergence of private art collecting and the art market in Buenos Aires from late 19th century up to the 1910s. In the absence of artistic institutions, like museums or academies, the Buenos Aires case is unique in Latin-America. Its art system was driven by art dealers and collectors. Local art commerce was developed in the city first through "bazaars" (unspecialized stores) and, at the end of the 19th century, through the installation of the first professional art galleries. Local art buyers favored European contemporary paintings and sculptures and made numerous purchases in renowned art galleries like the Paris-based Boussod, Valadon & Cie. Gallery. At the same time, foreign dealers and particularly the French State planned international exhibitions in order to profit from the acquisition power of the upper class in Buenos Aires and to develop a receptive market in the city.